Numerical Analysis of the Effect of Dynamic Viscosity Associated with a Continuously Moving Heated Horizontal Plate - M. A. Waheed; E. O. Sangotayo (Novel Perspectives of Engineering Research Vol. 6, 2022)
This work presents numerical simulations of the impact of altering dynamic viscosity coupled with viscous dissipation on convective heat transfer in a fluid-filled rectangular cavity. A hot horizontal plate maintained at temperature Tw and traveling at a constant velocity Uw at the top the cavity. Additionally, on the left vertical and lower horizontal sides, it is limited by cold isothermal walls, while on the right, it is bounded by an adiabatic vertical wall. A quenching media was injected into the cavity. The governing equations were converted to non-dimensional form and solved using a finite difference scheme numerical technique implemented in the C++ programming language. The study was conducted on a variety of fluids, including oil with a Prandtl number of 10, air with a Prandtl number of 0.7, and liquid metal with a Prandtl number of 0.01, for a variety of viscosities, parameters in the range 5*10-1 to 9*10-1, heat capacity in the range 1<Cp<10, fixed Eckert numbers, Ec = 1.0, and mixed convection parameter, Gr/Re2 = 1.0, and the finite difference approach was used to solve the flow regulating equations, which included the momentum and energy equations. Profiles are used to display the numerical findings generated. The results indicate that dynamic viscosity has a considerable effect on the velocity and temperature profiles when the specific heat capacity and Prandtl number are greater than unity and the viscous dissipation is fixed. Additionally, for Prandtl numbers greater than unity, increasing the dynamic viscosity results in a considerable drop in the fluid’s maximum velocity. The results will aid in the design of heat exchanger devices and serve as a baseline for manufacturing and material processing sectors involved in wire drawing, continuous rolling, and glass fiber production.